Answer:
![y^{-1} =\frac{1}{2} x-\frac{5}{2}](https://tex.z-dn.net/?f=y%5E%7B-1%7D%20%3D%5Cfrac%7B1%7D%7B2%7D%20x-%5Cfrac%7B5%7D%7B2%7D)
Step-by-step explanation:
Answer:
PREACH
Step-by-step explanation:
that is so smart :)
Answer:
all...
Step-by-step explanation:
<span>solve the equation ax – c = bx + d for x:
1) Group the x terms together on the left: ax - bx - c = d
2) Group the constant terms together: ax - bx = c + d
3) factor out x: x(a - b) = c + d
4) Divide both sides of the equation by (a - b) to obtain a formula for x:
c+d
</span> x(a - b) = c + d => x = ---------
a-b
This shows that the given equation CAN be solved for x, but there is a restriction: a must NOT equal b, because if a-b = 0, we'd have division by zero (which is not defined).
Where is Victoria's solution? Please share it if you want to discuss this problem further. Thank you.
Solve (2x - 1)(3x^2 - 9x - 4)
=